ANALISIS YURIDIS TENTANG PERWALIAN ANAK DALAM PRESFEKTIF UNDANG-UNDANG PERKAWINAN STUDI KASUS GALA SKY - MUTHAHHAR ASQALANI DATAU (Universitas Mahasaraswati K. Mataram, 2024)
Guardianship of children is an important aspect of the law relating to the protection and management of the interests of minors. In the context of Indonesian law, guardianship is regulated by various laws, including the Civil Code (KUHPerdata), Law Number 1 of 1974 concerning Marriage, and the Compilation of Islamic Law (KHI). The research used in this study is a normative juridical approach, with an analysis of relevant legislation and case studies related to child guardianship. The results of this analysis show that there is no clear definition of guardianship in the Marriage Law, but the conditions for guardianship can be found, namely one of the parents or both parents dying, parents divorcing, and parental authority being revoked. In guardianship, the principle of indivisibility is recognized so that the guardian of the child is only one, departing from this idea, the guardian of the child for Gala Sky is only one, but to whom the guardianship is assigned will await the decision of the Panel of Judges in the Court